Prenatal Diagnosis of Autosomal Dominant Polycystic Kidney Disease: Case Report - Elitsa Gyokova; Eleonora Hristova-Atanasova; Elizabeth Odumosu; Antonia Andreeva (Reports)
Background and Clinical Significance: Polycystic kidney disease (PKD) is the most common inherited kidney condition, affecting approximately 500,000 individuals in the US. It causes fluid-filled cysts to develop throughout the kidneys, leading to decreased kidney function. Autosomal dominant polycystic kidney disease (ADPKD) is the more prevalent form, subdivided into the PKD1 and PKD2 variants. PKD1 variants typically result in more severe symptoms and an earlier need for dialysis compared to PKD2. A prenatal diagnosis of ADPKD is rare due to its late-onset manifestations, but early detection can be crucial for management and family counseling. Case Presentation: A 24-year-old woman, during her first pregnancy, presented for her first prenatal ultrasound at 22 + 2 weeks gestation. The ultrasound revealed an increased echogenicity of the renal parenchyma in the left kidney, with pelvic dystopia, while the right kidney appeared normal. Follow-up scans showed significant progression, with both kidneys exhibiting thinning parenchyma and cyst formation. The baby was delivered via an elective cesarean section at 38 weeks, and a postnatal ultrasound confirmed ADPKD. Genetic testing identified a heterozygous variant of the PKD1 gene, NM_001009944.3 (PKD1):c.9157G>A p.(Ala3053Thr), classified as likely pathogenic. The baby displayed electrolyte abnormalities but improved after a week of hospitalization. Conclusions: This case highlights an unusual early presentation of ADPKD in a fetus with no family history of the disease. A prenatal diagnosis through ultrasounds and genetic testing can aid in early detection and management, providing valuable information for family counseling. Regular monitoring and genetic identification are essential for managing ADPKD and improving patient outcomes.